2018
DOI: 10.1002/jum.14674
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dissipative Energy Loss Detected by Vector Flow Mapping in Children: Characteristics of Normal Values

Abstract: The present study initially validated the application of vector flow mapping-derived EL analysis in right ventricle and established reference values for the future assessment of children with cardiopulmonary disease. Age, heart rate, and strain were independent variables correlated with the dissipative EL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Vector flow imaging performed intraoperatively has been used to quantify flow complexity using methods such as vector concentration which has exhibited a strong correlation to degree of stenosis (13). Additionally, vector flow imaging has been used for pressure gradient estimations at the carotid bifurcation and at the aortic valve, along with vorticity estimations in the ascending aorta and carotid bulb (14,15,16). The study of vortex formation in the cardiac chambers has also been demonstrated with vector flow mapping and vector flow imaging (17).…”
Section: Discussionmentioning
confidence: 99%
“…Vector flow imaging performed intraoperatively has been used to quantify flow complexity using methods such as vector concentration which has exhibited a strong correlation to degree of stenosis (13). Additionally, vector flow imaging has been used for pressure gradient estimations at the carotid bifurcation and at the aortic valve, along with vorticity estimations in the ascending aorta and carotid bulb (14,15,16). The study of vortex formation in the cardiac chambers has also been demonstrated with vector flow mapping and vector flow imaging (17).…”
Section: Discussionmentioning
confidence: 99%
“…The age characteristics of the subjects and results of the cardiac ultrasound studies are summarized in Table 2 [28,29,44,[58][59][60][61].…”
Section: Effect Of Age In Cardiac Ultrasound Studiesmentioning
confidence: 99%
“…Chen et al [61] used VFM to study 90 healthy children aged 1-18 years, which were divided into 3 age groups. The average diastolic and systolic ELs were calculated for the RV in the RV-focused apical 4-chamber view and for the RV outflow tract and pulmonary trunk (OP) in the parasternal short-axis view.…”
Section: Ultrasound Studies: Right Ventriclementioning
confidence: 99%
“…Lastly, in the analysis of right ventricle (RV) EL in children, median values for diastolic and systolic EL were 8.82 W/m and 3.17 W/m, and at multivariate analysis age was identified as the strongest influencing factor for EL. 24…”
Section: Reference Values and Correlations With Standard Doppler Parametersmentioning
confidence: 99%